2016
DOI: 10.1108/jsm-04-2015-0156
|View full text |Cite
|
Sign up to set email alerts
|

Co-production of service experiences: insights from the cultural sector

Abstract: Purpose The increased involvement of customers in their experience is a reality for all service organisations. The purpose of this paper is to explore the way organisations collaborate with customers to facilitate consumption of cultural experiences through the lens of co-production. Although organisations are typically an integral part of the co-production process, co-production is typically considered from a consumer angle. Aligned with the service ecosystem perspective and value-in-cultural context, this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 65 publications
(91 reference statements)
0
32
0
Order By: Relevance
“…servitization (Bititci et al 2012;Ng et al 2012;Vargo and Lusch 2008). Organizations engage with their customers through intricately related processes over time (Minkiewicz et al 2016); business models of firms and their practices are interactively connected (Heikkilä et al 2014;Holttinen 2014) and (re)designed (Frow et al 2015;Nenonen and Storbacka 2010). Organizations engage with their customers through intricately related processes over time (Minkiewicz et al 2016); business models of firms and their practices are interactively connected (Heikkilä et al 2014;Holttinen 2014) and (re)designed (Frow et al 2015;Nenonen and Storbacka 2010).…”
Section: Marketing Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…servitization (Bititci et al 2012;Ng et al 2012;Vargo and Lusch 2008). Organizations engage with their customers through intricately related processes over time (Minkiewicz et al 2016); business models of firms and their practices are interactively connected (Heikkilä et al 2014;Holttinen 2014) and (re)designed (Frow et al 2015;Nenonen and Storbacka 2010). Organizations engage with their customers through intricately related processes over time (Minkiewicz et al 2016); business models of firms and their practices are interactively connected (Heikkilä et al 2014;Holttinen 2014) and (re)designed (Frow et al 2015;Nenonen and Storbacka 2010).…”
Section: Marketing Approachmentioning
confidence: 99%
“…Value propositions are interactively shaped (Ballantyne et al 2011;Martinez and Bititci 2006). Organizations engage with their customers through intricately related processes over time (Minkiewicz et al 2016); business models of firms and their practices are interactively connected (Heikkilä et al 2014;Holttinen 2014) and (re)designed (Frow et al 2015;Nenonen and Storbacka 2010). Relationships among firms in a network are believed to promote interaction, mutual orientation and thereby value (Grönroos 2015;Kothandaraman and Wilson 2001).…”
Section: Marketing Approachmentioning
confidence: 99%
“…The best evaluators of product-service are the customers who experience services while not the service staff that provide services (Minkiewicz et al, 2016). So the productservice performance is evaluated based on perceived value from customers.…”
Section: Discussion On Evaluation Methodsmentioning
confidence: 99%
“…The findings of Minkiewicz et al (2016) can also be confirmed; service failures occur mostly when the group is made up of different cultural groups as, in the case of Route 1, the different needs of those with and without disabilities were not considered. As a result, it proved difficult to keep the group unified and not divided by type of disability.…”
Section: Theoretical Implicationsmentioning
confidence: 96%